2021
DOI: 10.52547/archhygsci.10.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment and Determination of Heavy Metal Contamination in Barley Grains in Khuzestan Province, Iran

Abstract: Background & Aims of the Study: Heavy metal pollution has become a global problem, and their entry into the food chain is considered a threat to humans and other organisms. This study aimed to assess the risk of metals (chromium, nickel, arsenic, copper, zinc, cadmium, and lead) in edible barley grains grown in Khuzestan Province, Iran, in 2019. Materials and Methods:In this analytical study, five farms of edible barley grains were selected. Then, four stations were selected in each farm. After sampling, barle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Some people also conducted quantitative research on different sources of soil heavy metals in Beijing [7]. Fouladi et al used the MCR-WALS model to calculate quantitatively that contribution rates of atmospheric deposition, fertilizers and pesticides, and natural sources to soil heavy metals accounted for 15.5%-16.4%, 5.9%-7.7%, and 76.0%-78.6%, respectively, indicating that natural sources dominated soil heavy metals in Beijing as a whole [8]. Jwad and Abbas investigated the soil heavy metals (Cd, Hg, Cu, and Zn) in a vegetable base in North China, and showed that the average content of each heavy metal in this area did not exceed the second-level soil quality standard.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some people also conducted quantitative research on different sources of soil heavy metals in Beijing [7]. Fouladi et al used the MCR-WALS model to calculate quantitatively that contribution rates of atmospheric deposition, fertilizers and pesticides, and natural sources to soil heavy metals accounted for 15.5%-16.4%, 5.9%-7.7%, and 76.0%-78.6%, respectively, indicating that natural sources dominated soil heavy metals in Beijing as a whole [8]. Jwad and Abbas investigated the soil heavy metals (Cd, Hg, Cu, and Zn) in a vegetable base in North China, and showed that the average content of each heavy metal in this area did not exceed the second-level soil quality standard.…”
Section: Literature Reviewmentioning
confidence: 99%